An anisotropic creep model for continuously and discontinuously fiber reinforced thermoplastics. (7th July 2020) - Fliegener, Sascha; Hohe, Jörg
Abstract: Objective of the present study is the definition and implementation of a constitutive creep model for fiber reinforced thermoplastics. Both, unidirectionally as well as discontinuously long fiber reinforced materials are considered. Assuming that creep deformation is restricted to the thermoplastic matrix, a three term Kelvin–Voigt formulation is employed as a base material model. For continuously unidirectionally fiber reinforced materials, the thermoplastic matrix is superimposed with a standard linear elastic model. For discontinuously long fiber reinforced thermoplastics, an anisotropic generalization of the original, isotropic Kelvin-Voigt model is proposed. Both models are implemented into a finite element program and validated against an experimental data base consisting of tensile creep experiments on neat matrix material, unidirectionally fiber reinforced material as well as discontinuously long fiber reinforced material with different fiber volume fractions. Different fiber orientations as well as different temperatures are considered. As a structural example for further validation, creep experiments on loading points for hybrid thermoplastic sandwich structures are performed and simulated numerically. In all cases, the experimental results and the numerical prediction are found in a good agreement.